2008
DOI: 10.1007/s00787-008-0695-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial into the effects of food on ADHD

Abstract: The aim of this study is to assess the efficacy of a restricted elimination diet in reducing symptoms in an unselected group of children with Attention deficit/hyperactivity disorder (ADHD). Dietary studies have already shown evidence of efficacy in selected subgroups. Twenty-seven children (mean age 6.2) who all met the DSM-IV criteria for ADHD, were assigned randomly to either an intervention group (15/27) or a waiting-list control group (12/27). Primary endpoint was the clinical response, i.e. a decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 30 publications
(50 reference statements)
4
84
1
2
Order By: Relevance
“…Thus far, prenatal exposure to maternal smoking (18), low birth weight, prematurity (19,20), and specific environmental exposures such as lead and organic pollutants (7) have been linked to ADHD. In contrast, research on dietary factors such as sugar, artificial food colorings, zinc, iron, and ω-3 fatty acids, has established only vague causality in ADHD (7), despite some hints of their therapeutic potential (21,22). An empirical elimination diet has indeed been shown to be effective in Apgar score at 5 min a 9 (1) 9 (1) Exclusively breast-fed (months) a 3 (2) 3 (2) Antibiotic treatment during the first 6 mo of life 13 (33) 7 (20) Weight at age of 13 y (kg) a 56 (12) 57 (12) Length at age of 13 y (cm) a 165 (9) 165 (9) Systolic blood pressure at the age of 13 (mmHg) a 104 (10) 106 (11) Waist circumference (cm) a 70 (8) 72 (10) Results are given as mean (SD) a or as number (%) of subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, prenatal exposure to maternal smoking (18), low birth weight, prematurity (19,20), and specific environmental exposures such as lead and organic pollutants (7) have been linked to ADHD. In contrast, research on dietary factors such as sugar, artificial food colorings, zinc, iron, and ω-3 fatty acids, has established only vague causality in ADHD (7), despite some hints of their therapeutic potential (21,22). An empirical elimination diet has indeed been shown to be effective in Apgar score at 5 min a 9 (1) 9 (1) Exclusively breast-fed (months) a 3 (2) 3 (2) Antibiotic treatment during the first 6 mo of life 13 (33) 7 (20) Weight at age of 13 y (kg) a 56 (12) 57 (12) Length at age of 13 y (cm) a 165 (9) 165 (9) Systolic blood pressure at the age of 13 (mmHg) a 104 (10) 106 (11) Waist circumference (cm) a 70 (8) 72 (10) Results are given as mean (SD) a or as number (%) of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, prenatal exposure to maternal smoking (18), low birth weight, prematurity (19,20), and specific environmental exposures such as lead and organic pollutants (7) have been linked to ADHD. In contrast, research on dietary factors such as sugar, artificial food colorings, zinc, iron, and ω-3 fatty acids, has established only vague causality in ADHD (7), despite some hints of their therapeutic potential (21,22). An empirical elimination diet has indeed been shown to be effective in Results are given as mean (SD) a or as number (%) of subjects.…”
mentioning
confidence: 99%
“…In several studies dietary interventions comprising elimination and restrictive diets have shown promise as effective treatments for ADHD (Nigg and Holton 2014;Stevenson et al 2014). Although it requires significant effort and is difficult to maintain long-term, positive effects have been found following the implementation of very restrictive diets, such as the "few foods" diet (Pelsser et al 2009). However, further research is required as the benefits of such interventions have been inconsistently confirmed in published meta-analyses.…”
Section: The Potential For Antioxidant-related Therapies In Adhdmentioning
confidence: 99%
“…Ser på effekten av automater i forhold til spisevaner Pelsser et al 2009 Behandling av barn med ADHD Ser på forskjeller i selvvurdert helse blant ungdommer Robinson-O'Brien et al 2010 Ingen relevante utfall (laering eller helse), sammenheng mellom å spise det ene og det andre... Rogers et al 2010 Ser på sammenheng mellom kosthold i barndom og sykdom/ikke skolemat, ikke skolesetting Ruottinen et al 2010 Ser på naeringsinnhold og effekten av det Tiltak: Bevisstgjøring og opplaering Singhal et al 2010 Tiltak er bevisstgjøring, ikke mattilbud St-Onge et al 2009 Ser på helseutfall i forhold til omlegging av diett hos barn. Story et al 2006 Vurdering av politikkutforming Suarez-Balcazar et al 2007 Systemendringer i skolen Ser ikke på relevante utfall Wojcicki and Heyman 2006 Vurderer utfall av politikk Omhandler Kina.…”
Section: Studieunclassified